Markedly reduced ventricular arrhythmia during the peripartum period in a pregnant woman with Andersen-Tawil syndrome - Chizuko A. Kamiya; Wataru Shimizu; Yoshinari Kabayashi; Takekazu Miyoshi; Chinami Horiuchi; Takashi Umekawa; Kaoru Yamanaka; Reiko Neki; Shinji Katsuragi; Jun Yoshimatsu; Tomoaki Ikeda (Journal of Arrhythmia, 2012)
Andersen-Tawil syndrome (ATS), also known as long QT syndrome type 7, is a rare autosomal dominant disease caused by a KCNJ2 mutation. The characteristic triad of ATS is periodic paralysis, dysmorphic features, and ventricular arrhythmia. We describe a case of a woman with Andersen-Tawil syndrome and a history of syncope whose pregnancy was complicated with frequent premature ventricular contractions (PVCs) and nonsustained ventricular tachycardia (NSVT). Her PVCs and NSVT were significantly decreased during the peripartum period, especially during labor. We treated her with beta-blockers throughout her pregnancy, and she experienced no complications. Although the mechanism underlying the decreased PVCs and NSVT in pregnancy has not been elucidated, women with ATS may have less arrhythmic event risk during pregnancy.